Orai1 and Stim1 regulate normal and hypertrophic growth in cardiomyocytes - Völkers, Mirko; Zielonka, Mareen; Herzog, Nicole; Frank, Derk; Dolatabadi, Nima; Frey, Norbert; Gude, Natalie; Friedrich, Oliver; Koch, Walter J.; Katus, Hugo; Sussman, Mark A.; Most, Patrick (Journal of molecular and cellular cardiology, 2010)
Cardiac hypertrophy is an independent risk for heart failure (HF) and sudden death. Deciphering signalling pathways dependent on extracellular calcium (Ca2+) influx that control normal and pathological cardiac growth may enable identification of novel therapeutic targets. The objective of the present study is to determine the role of the Ca2+ release-activated Ca2+ (CRAC) channel Orai1 and stromal interaction molecule 1 (Stim1) in postnatal cardiomyocyte store operated Ca2+ entry (SOCE) and impact on normal and hypertrophic postnatal cardiomyocyte growth.